HOW GEOPOLITICAL, CREDIT AND FINANCIAL RISKS DEFINE ASEAN BANKS’ PERFORMANCE? - Andriani, Evana; Ashsifa, Izza; Kuncoro, Muhammad Teguh (LPPM STIE Muhammadiah Bandung, 2024)
The banking sector is essential to the global economy, functioning as a central financial hub responsible for allocating funds, providing essential services, and assessing economic health. However, this pivotal role exposes banks to various risks, including geopolitical, credit, and financial risks. These risks arise from the banking sector’s role as a financial facilitator, its global reach, and its handling of complex financial instruments. A quantitative approach is employed in this research, utilizing multiple regression analysis to analyze the impact of geopolitical, credit and financial risks on bank performance in the ASEAN region. The data analyzed from 2013 to 2022, using a purposive sample yielding 690 samples, reveals that geopolitical risk, credit risk, and financial risk have a negative impact on bank performance. These findings offer valuable insights for policymakers and regulators, informing the development of targeted regulations to address the specific risk landscape faced by banks and potentially enhancing financial stability.